Innovative Models for Integrated Pediatric Care: Leveraging Nursing, Pharmacy, and Specialist Expertise in Saudi Arabia's Evolving Healthcare Landscape - Mansour Malahi Al-Harbi, Farah Farhan Raja Albanaqi, Salamah Rajan Aldhafeeri, Mohammed Abdullah Albadrani, Fahad Obaid Alshammari, Meshal Mohammed Alshammari, (Journal of International Crisis and Risk Communication Research, 2024)
As the healthcare landscape in Saudi Arabia evolves, innovative models for integrated pediatric care are emerging to address the unique needs of children and families. This article reviews the current literature on integrated pediatric care models that leverage the expertise of nursing, pharmacy, and specialist professionals in Saudi Arabia. The review aims to identify the key components, outcomes, and challenges of these models, and to provide recommendations for future research and practice. A comprehensive search of PubMed, Scopus, and Web of Science databases was conducted for studies published between 2010 and 2024, using keywords such as "pediatric care," "integrated care," "nursing," "pharmacy," "specialist," and "Saudi Arabia." A total of 18 studies met the inclusion criteria and were included in the review. The findings suggest that integrated pediatric care models that involve collaboration and coordination among nursing, pharmacy, and specialist professionals can improve access to care, patient satisfaction, clinical outcomes, and cost-effectiveness. The key components of these models include interprofessional communication, shared decision-making, care coordination, patient and family education, and technology-enabled care. The main challenges include workforce shortages, training and competency gaps, fragmented health information systems, and cultural and linguistic barriers. The review highlights the need for further research to evaluate the long-term impact and sustainability of these models, and to identify best practices for their implementation and scale-up in diverse healthcare settings in Saudi Arabia.